Bicycle-inspired simple balance control method for quadruped robots in high-speed running - Hattori, Shoei; Suzuki , Shura; Fukuhara , Akira; Kano , Takeshi; Ishiguro , Akio (Frontiers in Robotics and AI, 2025)
This paper explores the applicability of bicycle-inspired balance control in a quadruped robot model. Bicycles maintain stability and change direction by intuitively steering the handle, which induces yaw motion in the body frame and generates an inertial effect to support balance. Inspired by this balancing strategy, we implemented a similar mechanism in a quadruped robot model, introducing a yaw trunk joint analogous to a bicycle’s steering handle. Simulation results demonstrate that the proposed model achieves stable high-speed locomotion with robustness against external disturbances and maneuverability that allows directional changes with only slight speed reduction. These findings suggest that utilizing centrifugal force plays a critical role in agile locomotion, aligning with the movement strategies of cursorial animals. This study underscores the potential of bicycle balance control as an effective and straightforward control approach for enhancing the agility and stability of quadruped robots as well as potentially offering insights into animal motor control mechanisms for agile locomotion.